Utilization of Waste Denim Fibers in Asphalt Pavement: A Review - Gailan Ismat Safaeldeen (Genius Journals, 2023)
The purpose of this study is to discuss how waste denim fibers (WDF) can be utilized as a modifier in applications for green asphalt pavement construction. It was discussed where denim fiber comes from, what it is made of, and its characteristics. It also covered how WDF affected the rheological and physical characteristics of unmodified- and modifiedasphalt binders. The reasons for using denim fiber as a modifier for basic and modifiedasphalts were also emphasized, including its mechanical qualities, water content is lower than most of natural fiber, and sustainability in terms of low costs and simultaneous environmental problems mitigation. However, there are challenges to using WDF in the construction of pavements, including the design of the blending process, figuring out an easy, affordable way to dissolve the fiber in asphalt, and the presence of the water content of the fibers, which may influence the cohesion and adhesion performance of asphalt binders and mixtures. The research gaps and recommendations for future studies were also summarized in this short review. It seems likely that long-lasting, affordable, and ecofriendly denim fiber-modified asphalt and rut- and fatigue-resistant asphalt mixtures would be developed in the near future. This will lower the annual maintenance costs for flexible pavements that are needed all over the world
Keywords: Waste denim fiber; Asphalt; Waste materials